ANALISIS PENGARUH PERTUMBUHAN EKONOMI TERHADAP TINGKAT KEMISKINAN DI ACEH UTARA - Musrizal Musrizal (Politeknik Negeri Lhokseumawe, 2019)
Abstract : This study examines the effect of economic growth on poverty levels. The results of the regression analysis tend to support the hypothesis which indicates that economic growth influences the level of poverty. The data used are secondary data sourced from North Aceh BPS and the technical data analysis used is simple regression. Keywords: Poverty, Economic Growth